Children with complex needs and cochlear implants: The parent's perspective. (September 2013) - Mulla, Imran; Harrigan, Suzanne; Gregory, Sue; Archbold, Sue
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives This study qualitatively explored parents' perspectives on their experiences of, access to, and outcomes from, cochlear implantation for their child with complex needs. Methods Purposive sampling was used to recruit 10 parents of children with varying additional disabilities. The age range of the children was between 2 and 11 years at the time. A semi-structured interview format was used to collect data and the interviews were audio recorded and transcribed for analysis. Thematic content analysis was used to explore the data. Results Individual themes were clustered together to form four main themes describing parents' perspectives and experience. The four main themes were: 'Assessment process', 'Reported benefits of cochlear implantation', 'Wearing the processor' and 'Educational issues'. Discussion The findings from the study indicate how cochlear implantation was valued by the parents of children with complex needs. They appreciated changes in their child's communication and social changes where the child was more included in family life. Challenges relating to delays in the assessment process were reported. Similarly, the difficulties associated in accessing the technology were identified and perceived by some parents as discriminatory. Conclusion Cochlear implantation has come a long way over the years. This study provides a useful insight into the issues raised by parents of deaf children with complex needs. A need for further research in this area of implantation was identified to ensure wider access to this technology for those who may benefit from it and to improve the implantation process for this group of children.